Physiological responses to high-intensity interval exercise differing in interval duration - Tucker, W. J.; Sawyer, B. J.; Jarrett, C. L.; Bhammar, D. M.; Gaesser, G. A. (The Journal of Strength and Conditioning Research, 2015)
We determined the oxygen uptake (VO2), heart rate (HR), and blood lactate responses to 2 high-intensity interval exercise protocols differing in interval length. On separate days, 14 recreationally active males performed a 4 × 4 (four 4-minute intervals at 90-95% HRpeak, separated by 3-minute recovery at 50 W) and 16 × 1 (sixteen 1-minute intervals at 90-95% HRpeak, separated by 1-minute recovery at 50 W) protocol on a cycle ergometer. The 4 × 4 elicited a higher mean VO2 (2.44 ± 0.4 vs. 2.36 ± 0.4 L/min) and "peak" VO2 (90-99% vs. 76-85% VO2peak) and HR (95-98% HRpeak vs. 81-95% HRpeak) during the high-intensity intervals. Average power maintained was higher for the 16 × 1 (241 ± 45 vs. 204 ± 37 W), and recovery interval VO2 and HR were higher during the 16 × 1. No differences were observed for blood lactate concentrations at the midpoint (12.1 ± 2.2 vs. 10.8 ± 3.1 mmol/L) and end (10.6 ± 1.5 vs. 10.6 ± 2.4 mmol/L) of the protocols or ratings of perceived exertion (7.0 ± 1.6 vs. 7.0 ± 1.4) and Physical Activity Enjoyment Scale scores (91 ± 15 vs. 93 ± 12). Despite a 4-fold difference in interval duration that produced greater between-interval transitions in VO2 and HR and slightly higher mean VO2 during the 4 × 4, mean HR during each protocol was the same, and both protocols were rated similarly for perceived exertion and enjoyment. The major difference was that power output had to be reduced during the 4 × 4 protocol to maintain the desired HR.